APLIKASI UNLALIA BATIK TROSO BERMUATAN EMPAT KETERAMPILAN BERBAHASA SEBAGAI INOVASI PEMBELAJARAN SISWA KELAS VIII SMP/MTs - Novi Auliana Putri; Muhammad Noor Ahsin; Luthfa Nugraheni (Balai Bahasa Sumatera Utara, 2022)
In learning Indonesian at SMP/MTs Kudus, there are not many students use android-based media. Even though Android-based learning media is important, especially for persuasion material which includes four aspects of language skills. This study aims to analyze the needs of students and teachers in the use of learning media and then describe the development of the Unlalia Batik Troso application which contains four aspects of language skills. The research method used is Research and Development which uses the theory of Sukmadinata of three stages of development. The subjects in this study are 110 students consisting of: 32 students from SMP N 1 Undaan Kudus, 40 students from Mu'allimat NU Kudus, and 38 students from MTs NU Assalam Jati Kudus. Students and teachers state that learning media is important in the Indonesian language learning process. This can be seen from the results of the needs analysis with the percentage of 67% of Indonesian teachers stating that they really need learning media and 33% stating that there is a need for learning media. The results of the analysis of student needs are that 92% of students really need application learning media and 8% of students say they need application media. While the results of the development of the Unlalia Batik Troso application prototype utilize several supporting applications, namely Canva, CapCut, Microsoft PowerPoint, and Smart Apps Creator.